PKM Empowerment and Legal Protection of Gamelan Craftsmen of UD Kayu Mas, Dangin Puri Village, East Denpasar District, Denpasar City - Desak Gde Dwi Arini; Ni Gusti Ketut Sri Astiti; Ni Ketut Sukiani (Community Service Journal of Law, 2025)
Dangin Puri Village, located in East Denpasar, Denpasar City, Bali Province, covers an area of 0.65 km² with a population of 8,846 people (2021). This village holds significant potential for economic development through the empowerment of micro, small, and medium enterprises (MSMEs) in sectors such as handicrafts, culinary, and services. However, many local MSMEs still lack understanding and utilization of digital technology, which hinders their business growth. One notable example is UD Kayu Mas, a traditional gamelan handicraft enterprise that has not yet registered its creations under copyright law, leading to unclear legal protection and limited market expansion. Additionally, the craftsmen’s limited digital literacy and inadequate access to technological tools pose challenges in adopting digitalization. To address these issues, community service activities were carried out to socialize the importance of copyright registration and digital empowerment. The program introduced legal awareness through the registration of gamelan and gender laras nada gending in the form of plawah, unique to UD Kayu Mas. Empowerment initiatives involved students who practiced at UD Kayu Mas and supported the establishment of the Swasti Swara studio in Denpasar. The program also included digital training, such as creating online business profiles, using social media platforms (Instagram, Facebook), and utilizing online marketplaces for product marketing. The outcomes included improved legal awareness, better understanding of digitalization benefits, and enhanced digital skills among craftsmen. These efforts are expected to expand market reach, increase sales, and promote operational efficiency. The results were disseminated through an international journal publication, print media, and a four-minute promotional video on YouTube.